GEN Z AND RELIGIOUS-BASED SOCIAL DISTANCE - Hapsari Dwiningtyas Sulistyani; Turnomo Rahardjo; Lintang Ratri Rahmiaji (Profetik: Jurnal Komunikasi, 2021)
Gen Z is the generation that were born between 1996 and 2015. In this paper the gen z is represented by university students who become the respondents of this research. The main focus of this paper is describing the religion-based social distance among the university students. Social distance is the degree of separation between different social groups. The specific group this paper focuses on is the religion-based groups. The main theory employs in this research is Social Scale theory that provide the basic instrument of social distance measurement. To gather the data this research uses survey and interviews. The result depicts that there are social distances on particular religious groups. The percentages of respondents who feel a distance to certain religious groups are varied. The percentages of respondent who perceived a distance toward Islam is only 7,5 percent. Whereas the percentage that of social distance to local religions, on the other hand, is staggering on the value 84,3 percent. The result signifies that most of respondent feel that they have a social distance to local religious groups. The respondent argues that the main reason for the social distance toward the local religious group is the perception that the local religious believers are more likely to form a cult that might be endangered the social harmony in the university.